Necesidad de reformar el código de trabajo en lo referente a la obligación de los empleadores en el trabajo subterráneo, de realizar el examen médico de aptitud a los trabajadores y llevar un registro de personal sin discriminación de edad. - González Sigcho, Gualquiria María (2011)
Constitution of the Republic of Ecuador, guarantees the right to health and personal integrity as fundamental rights of individuals, and for establishing the right of workers to develop their activities in a supportive environment that protects their health and integrity. However, in Ecuador, activity is by its very nature presents many risks to health and safety of workers underground work. In revising the Labour Code, I can determine the existence of legal problems, which deal mainly with the fact that establishing that the medical examination of fitness and personal record will be made only to employees under twenty years age, thus leaving unprotected those who are older than the aforementioned. The situation under labor law is undoubtedly a legal uncertainty which undermines the validity of the right to health and means discrimination also affects the right to equality before the law, which is also recognized as a fundamental right of all people. The previous problem is studied in this research work, which collect more than all the theoretical and factual information about the problem in question, also advanced to the approach of a legal proposal to guarantee efficiently underground workers' rights .